The Effect of Stress Inoculation Training (SIT) on Depression and Quality of Life in Multiple Sclerosis (MS) Patients with Control of Duration of Disease in Esfahan City - Sadighe Sadeghi; Mahnaz Mehrabi Zadeh Honarmand; Najmeh Hamid (Majalah-i ̒ilmī pizishkī-i jundī/shapūr, 2012)
Background and Objective: The aim of this research was to study the effect of stress inoculation training (SIT) on depression and quality of life in Ms Patients.Subjects and Methods: The research method was experimental with pre-post test and control group. The original samples consisted of 83 Patients who were selected from Isfahan MS association. They were matched from age, sex, educational status, duration of MS disease, depression and other criteria considered in this research. They were randomly divided into two groups as experimental and control. The instruments were BDI and MSIS-29 Scales. We used MANOVA to analyze the data.Results: The results indicated that there was a significant difference between two groups (p<0.001). The rate of depression decreased and the quality of life increased significantly in experimental group in comparison with the pre test and control group. Conclusion: Stress inoculation training (SIT) decreased the depression and increased the quality of life in MS Patients. Therefore, it is recommended to use this method for MS Patients.